Production and Evaluation of Mosquito Repellent Dhoop from Orange Peels oil - Ibrahim Hussaini; Hussaina Aminu Ibrahim; Abdullahi Jibril Musa (Biology, Medicine, & Natural Product Chemistry, 2026)
This study explores the extraction of limonene oil from orange peels using Soxhlet extraction with petroleum ether as the solvent, yielding 9.88%. The limonene oil was utilized to formulate a natural mosquito repellent dhoop by incorporating turmeric, camphor, and activated charcoal. Evaluation methods including cage tests, mosquito landing tests, fume tests, toxicity tests, and skin irritability tests demonstrated the dhoop’s effectiveness in repelling mosquitoes, its non toxic nature, and its safety for human use. Infrared (IR) spectral analysis confirmed the presence of key functional groups, such as terpenoids and phenolic compounds, contributing to the dhoop’s repellant efficacy. The study highlights the potential of orange peel waste as a sustainable source for natural repellents, promoting eco-friendly alternatives to synthetic products. The findings underscore the dhoop’s effectiveness, safety, and environmental sustainability, offering a viable solution for mosquito control and waste valorization. Recommendations include scaling up production, optimizing formulations, and exploring additional applications of limonene oil.